Relationship between the Hadamard Theorem on Three Disks and Certain Problems of Polynomial Approximation of Analytic Functions - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
By using the classical Hadamard theorem, we obtain an exact (in a certain sense) inequality for the best polynomial approximations of an analytic function f(z) from the Hardy space H p, p ≥ 1, in disks of radii ρ, ρ1, and ρ2, 0 < ρ1 < ρ < ρ2 < 1.